2023
DOI: 10.3390/fermentation9040323
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lactic Acid Bacteria Additives on Fatty Acids, Amino Acids and Antioxidant Capacity of Leymus chinensis Silage during Aerobic Exposure

Abstract: During aerobic exposure of silage, the fatty acid and amino acid composition may alter the quality and palatability, resulting in economic losses in livestock production. The objective of this study was to evaluate the effects of Lactiplantibacillus plantarum (LP), Lenti Lentilactobacillus buchneri (LB), and a mixture of LP and LB (PB) on the fatty acids, amino acids, and antioxidant capacity of Leymus chinensis silage during aerobic exposure. The lactic acid bacteria were added at 1 × 106 CFU/g. The silage tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
1
2
0
Order By: Relevance
“…The activity of lipoxygenases was highly sensitive to pH, with an optimum pH of 6.5, and it showed activity to pH within the range of 4.5 to 8.0 (Aanangi et al, 2016 ). In the present study, the LP_PP_SB-treated group exhibited the lowest pH (4.26), which could inhibit lipoxygenase activity more effectively than other treated groups and the control group (pH 4.44–5.30), resulting in the production of more PUFA content, which is consistent with the findings of a previous study (Liu et al, 2023 ). However, the results of a previous study were contrary to our results; inoculants of Lactobacillus buchneri or L. plantarum decrease the content of PUFAs as LABs have the ability to promote the biohydrogenation of fatty acids (Liu et al, 2018 ).…”
Section: Discussionsupporting
confidence: 92%
“…The activity of lipoxygenases was highly sensitive to pH, with an optimum pH of 6.5, and it showed activity to pH within the range of 4.5 to 8.0 (Aanangi et al, 2016 ). In the present study, the LP_PP_SB-treated group exhibited the lowest pH (4.26), which could inhibit lipoxygenase activity more effectively than other treated groups and the control group (pH 4.44–5.30), resulting in the production of more PUFA content, which is consistent with the findings of a previous study (Liu et al, 2023 ). However, the results of a previous study were contrary to our results; inoculants of Lactobacillus buchneri or L. plantarum decrease the content of PUFAs as LABs have the ability to promote the biohydrogenation of fatty acids (Liu et al, 2018 ).…”
Section: Discussionsupporting
confidence: 92%
“…Meanwhile, the ammonia nitrogen content in the LP group was also lower than that in CK, demonstrating that the LP used in this experiment has the ability to inhibit aerobic spoilage of corn silage and reduce protein decomposition and further confirming why LP can improve aerobic stability. Soluble sugars are one of the major components of plant silage fermentation ( Liu et al., 2023 ). In the present study, the soluble sugar content in silage feed inoculated with BV and LP was higher than that in CK.…”
Section: Discussionmentioning
confidence: 99%
“…High-moisture corn silage had low proportions of n-3 fatty acids, and although the additives exhibited differential effects between the two hybrids during fermentation, their effect was generally small. Previous studies have shown that field wilting ( 41 ), fermentation temperature ( 42 ), and additives ( 43 , 44 ) can all impact n-3 fatty acids in silage. Additionally, Li et al ( 45 ) reported that three strains of L. plantarum had differential effects on the fatty acid profile of alfalfa silage.…”
Section: Discussionmentioning
confidence: 99%